FILOSOFI ORANG SUCI HINDU DAN PERAN KEPEMIMPINAN HINDU - I Ketut Subagiasta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
This paper described about “The philosophy the holy man and the role of leadership of Hinduism”. Some explanation about its namely about the philosophy the priest of Hidu, some names the priest of Hindu, the role of priest of Hindu, and the duty of piest of Hindu, also about existence the priest of Hindu. Then also described about the philosophy leadership of Hindu, the role of the Hindu leadership, teaching the Hindu leadership, some efforts Hindu leadership in the connect in the quality human resourses of Hindu, and also about the sinergy Hindu leadership in the depelovment of physical and nonphysical.